Ageing with Smartphones in Urban Brazil A work in progress - Duque, Marília (Ageing with Smartphones, 2022)
With people living longer all over the world, ageing has been framed as a socio-economic problem. In Brazil, older people are expected to remain healthy and autonomous while actively participating in society. Based on ethnographic research in São Paulo, Ageing with Smartphones in Urban Brazil shows how older people in a middle-class neighbourhood conciliate these expectations with the freedom and pleasures reserved for the Third Age. Work is what bonds this community together, providing a sense of dignity and citizenship. Smartphones have become of great importance to the residents as they search for and engage in new forms of work and hobbies. Connected by a digital network, they work as content curators, sharing activities that fill their schedule. Managing multiple WhatsApp groups is a job in itself, as well as a source of solidarity and hope. Friendship groups help each to download new apps, search for medical information and guidance, and navigate the city. Together, they are reinventing themselves as volunteers, entrepreneurs and influencers, or they are finding a new interest that gives their later life a purpose. The smartphone, which enables the residents to share and discuss their busy lives, is also helping them, and us, to rethink the very representation of ageing.